(untitled) (Research, Society and Development, 2021)
Academic interest in problematizing gender normativity increased considerably at the end of the 20th century, influenced by gender and queer theorists. Consequently, studies on cis divergent identities are increasing, such as that of Brazilian transvestites. Transvestites subvert the binary gender by incorporating aspects of femininity to others socially considered masculine, such as having a penis. By highlighting the possibility of moving between two poles that the gender system considers mutually exclusive, interest arises in knowing the ways in which border crossings are present in transvestite experiences. Therefore, this article uses bibliographic research and has the general objective of discussing the importance of border transits in the transvestite identity construction, using a symbolic and geopolitical concept of border. In this way, the specific objectives of this proposal are to discuss transvestites, address the influence of urban centers on the transformation process of transvestites, understand the prestige of the European emic category. It concludes that different types of border displacement integrate relevant stages of the transvestite existence, because it is through these transits that they acquire cultural and financial capital that provides them, in addition to prestige, better living conditions.